Early Discharge of Newborns Born to Mothers with COVID-19: A Possible Safe Strategy - Costa, Simonetta; Coppola, Maria; Fattore, Simona; Tana, Milena; Gassino, Lisa; Catalano, Paola; Pastorino, Roberta; Vento, Giovanni (American Journal of Perinatology, 2023)
Objective In this study, we evaluated the safety of early discharge (ED) of newborns born to coronavirus disease 2019 (COVID-19)-positive mothers.Study Design All ED newborns from the postpartum wards of the Fondazione Policlinico Gemelli between January 1, 2022, and February 28, 2022, were retrospectively analyzed. Newborns from mothers with COVID-19 and those from uninfected mothers were considered. The primary outcome was to evaluate whether the rate of the composite outcome, which was the percentage of rehospitalization/access in emergency room (RH/ER) within the first week from discharge, differed between neonates born to mother with COVID-19 (COVID-19 group) and those born to uninfected mothers (no COVID-19 group). The secondary outcomes were to assess the quality of feeding and number of outpatient visits in the follow-up clinic between the two cohorts of patients.Results One hundred and thirty-four newborns in the no COVID-19 group and 26 in the COVID-19 group were analyzed. The rate of RH/ER in the no COVID-19 group was of 6 over 134 newborns (0.045, 95% confidence image [CI]: 0.017–0.095), while in COVID-19 group, it was of 2 over 26 newborns (0.077), which does not differ from the expected rate (1.17 over 26 newborns, 0.045, 95% CI: 0.017–0.095).Conclusion ED for newborns from mothers with COVID-19 could be an actionable safe strategy.Key Points
Keywords: COVID-19; early discharge; infants; pregnancy; rehospitalization